Antenatal Care Predicts Neonatal Mortality in Eastern Africa: A Systematic Review and Meta-analysis of Observational Studies. Issue 1 (March 2022) - Tiruye, Getahun; Shiferaw, Kasiye; Shunu, Addisu; Sintayeu, Yitagesu; Seid, Abdulbasit Musa
Background: Sub-Saharan African countries, especially the Eastern region, present the dismal picture of neonatal mortality (NM) in the globe. The majority of these deaths could be avoided if effective health measures are provided throughout pregnancy and childbirth. Although antenatal care (ANC) is assumed as one of the viable interventions that contribute to neonatal survival, the effect of ANC on NM was not systematically analyzed in Eastern Africa. Thus, the study aimed to determine the pooled effect of ANC on NM in Eastern Africa. Methods: PubMed, EMBASE, CINAHL, and HINARI databases were searched using appropriate keywords from January 1, 1990 to February 12, 2021. Independent authors selected eligible articles and extracted data. The risk of a bias assessment tool for nonrandomized studies was used to assess the quality of the study. Comprehensive meta-analysis version 2 was used for meta-analysis. The random-effect model was employed, and the outcome is expressed as a risk ratio with 95% confidence interval (CI). Results: In total, 1149 studies were identified through database search, and only 27 studies were included in the meta-analysis. Having at least 1 ANC visit during pregnancy reduced the risk of neonatal death by 42% compared to their counterparts (RR = 0.58, 95% CI [0.47, 0.71]). The pooled prevalence of NM was 8.5% (95% CI [7.3, 9.6]), with NM rate of 46.3/1000 live births. Conclusion: The study indicated that NM might be decreased even with a single ANC visit when compared to no visits. Scaling up ANC services through ANC promotion and tackling service-related barriers could potentially reduce NM in Eastern Africa.